How to survive history : how to outrun a Tyrannosaurus, escape Pompeii, get off the Titanic, and survive the rest of history's deadliest catastrophes - Cassidy, Cody (Penguin Books, an imprint of Penguin Random House LLC, 2023)
"History is the most dangerous place on earth. From dinosaurs the size of locomotives to meteors big enough to sterilize the planet, from famines to pandemics, from tornadoes to the Chicxulub asteroid, the odds of human survival are slim but not zero-at least, not if you know where to go and what to do. In each chapter of How to Survive History, Cody Cassidy explores how to survive one of history's greatest threats: getting eaten by dinosaurs, being destroyed by the asteroid that wiped out the dinosaurs, succumbing to the lava flows of Pompeii, being devoured by the Donner Party, drowning during the sinking of the Titanic, falling prey to the Black Death, and more. Using hindsight and modern science to estimate everything from how fast you'd need to run to outpace a T. rex to the advantages of different body types in surviving the Donner Party tragedy, Cassidy gives you a detailed battle plan for survival, helping you learn about the era at the same time. History may be the most dangerous place on earth, but that doesn't mean you can't visit. You can, and you should. And with a copy of How to Survive History in your back pocket, you just might make it out alive"--